1990
DOI: 10.1002/hon.2900080503
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing lymphadenitis: A review of clinicopathological, immunohistochemical and ultrastructural studies

Abstract: Necrotizing lymphadenitis (NEL) has been reported to be a reactive process described under differing terminology by Fujimoto et al. (1972), Kikuchi (1972), Wakasa et al. (1973) and other Japanese pathologists. Recently, this type of lymphadenitis has also been reported in America and Europe. In Japan, NEL is observed more frequently in the northern area, however, no characteristic seasonal occurrence has been noted. The disease affects young females more than males, particularly from the third and fourth decad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0
2

Year Published

1991
1991
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 7 publications
0
43
0
2
Order By: Relevance
“…[11][12][13][14]16 KFD is more prevalent in Asians, particularly in Far East nations including Korea. [5][6][7][8][9][10] Tanaka et al 9 reported that 2 HLA class II Cervical lymphadenopathy and fever are the most common presentations of the disorder. However, the clinical presentation may vary from patient to patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13][14]16 KFD is more prevalent in Asians, particularly in Far East nations including Korea. [5][6][7][8][9][10] Tanaka et al 9 reported that 2 HLA class II Cervical lymphadenopathy and fever are the most common presentations of the disorder. However, the clinical presentation may vary from patient to patient.…”
Section: Discussionmentioning
confidence: 99%
“…Although lymphadenopathy usually affects the cervical lymph nodes, the axillary lymph nodes and lymph nodes in other regions can be affected. [3][4][5][6][7][8][9][10]14,19 The size of the affected lymph nodes usually are 2 to 3 cm, but sometimes these nodes can be Ͼ5 cm. An affected lymph node is solid, movable, and painful but not suppurative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients with Kikuchi disease have a normal blood count [8], even though leukopenia is observed in 20-32% [9,21]. Atypical lymphocytes are reported in up to 25% of patients [18].…”
Section: Laboratory Testsmentioning
confidence: 99%
“…One ultrastructural study proposed that Kikuchi's syndrome reflects a self-limited, SLE-like autoimmune condition which is caused by virus-infected transformed lymphocytes [8]. In reviews, some patients who were initially diagnosed with Kikuchi's disease were reported to have subsequently developed systemic lupus erythematosus, and an ANA test should be performed in patients with suspected Kikuchi's syndrome in order to exclude this diagnosis [9,10]. Examination of the lymph node histopathology, in correlation with the clinical features, helps in differentiating SLE from KFD.…”
mentioning
confidence: 99%